The Inequality of Material Living Conditions in EU Countries - Ona Gražina Rakauskienė; Lina Volodzkienė (Economics & Sociology)
Socio-economic inequality has become one of the most relevant problems in the global economy. Studies carried out in the past 10 years have revealed that a high level of inequality prevents economic growth. The standard means of measuring these differences in equality include methods and aspects such as looking at inequalities in income and consumption, but these criteria do not reflect the actual level of inequality. To find out the actual level of socio-economic inequality, the distribution of wealth should be analysed. However, until now aspects involving the unequal distribution of material living conditions and housing inequality have not been the main objects of sufficient scientific research. For this reason, the main aspects to be analysed in this article are the distribution of material living conditions and housing inequality in Lithuania and other EU countries, with a special focus on the extent and volatility of the problem.